Thermal properties and phase stability of Yttria-Stabilized Zirconia (YSZ) coating deposited by Air Plasma Spray onto a Ni-base superalloy (2017)
Thermal properties and microstructure characterization of Yttria Stabilized Zirconia (YSZ) Thermal Barrier Coatings (TBCs) deposited by Air Plasma Spray (APS) onto a Ni-base superalloy (Inconel 625) were studied. Two separate sets of tests were performed. The first one consisted in Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) performed over free-standing TC samples detached from TBCs. The second one included the analysis of the cross section of samples heat treated at 1100. °C with holding times of 600, 1000, and 1700. h. The TC porosity was analyzed for different heat treatment conditions so that inter-lamellar, intra-lamellar and globular pores, as well as cracks, were identified and quantified independently. An initial porosity reduction related to inter-lamellar and intra-lamellar pores, as well as cracks, was observed during the first 600. h of heat treatment, due to sintering. However, porosity continually increased during heat treatment from 600 to 1700. h driven by volumetric changes associated to phase transformations. During this period, yttrium diffused from the metastable tetragonal phase favoring the transformation to cubic phase while monoclinic phase transformed after cooling from the yttrium-depleted tetragonal phase. Energy absorption curves and the variation of heat capacity with temperature were also determined and correlated to microstructural changes. © 2017 Elsevier Ltd and Techna Group S.r.l.